Does Ethical Leadership Moderate Internal Control and the Levers of Control on Performance?: A Study of Village Credit Institutions (LPD) in Denpasar City - I Gusti Ayu Asri Pramesti; Sistya Rachmawati; Etty Murwaningsari (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
Companies or organizations, particularly Village Credit Institutions (LPD), need special attention due to the observed decline in performance across various cases. Therefore, this study focuses on the internal control system, management control system, levers of control, and their impact on organizational performance, moderated by ethical leadership. This research intends to look into the significant impact of these variables on organizational performance, particularly when moderated by ethical leadership. Sampling was conducted using a purposive method and hypothesis testing adopted the Structural Equation Modeling method utilizing the application of Partial Least Square. The findings indicated that the internal control system and management accounting system contribute positively to organizational performance, while the levers of control indicated no significant influence. Additionally, ethical leadership failed to augment the effect of the variables on organizational performance. This research holds crucial implications for LPD, emphasizing the importance of controlling activities through policies and procedures to enhance performance.